CAN SYSTEMS ENGINEERING SUPPORT AN OWNER OPERATOR ORGANISATION WHEN FACED WITH THE CHALLENGE OF BEING A DESIGN AUTHORITY?. Issue 2 (July 2017) - Cowper, Doug; Krolikowski, Andrew; Gallagher, Ian; McGrogan, Nick
ABSTRACT: Over the years, acquisition methodologies, such as best value procurement (BVP), have resulted in a shift in engineering procurement where large organisations increasingly ask their supply chain to take on the responsibility for part of, or overall, system design. However, just handing over a set of requirements to a supplier and then waiting for them to deliver is a high‐risk strategy especially with novel/complex programmes. To reduce the risk of problems and to comply with some regulatory environments, the intelligent customer needs to take design responsibility, focusing on technically assuring that the system will be fit for purpose. This paper explores the issues facing an owner operator who needs to be the design authority, identifies aspects of systems engineering that require further work to support an owner design authority, and shows how systems engineering can support a design authority on a complex systems programme, in such a shared design management arrangement and regulated environment.